Antibody development and disease severity of COVID-19 in non-immunised patients with rheumatic immune-mediated inflammatory diseases: data from a prospective cohort study. Issue 1 (5th April 2022) - Boekel, Laura; Hooijberg, Femke; Vogelzang, Erik H; Besten, Yaëlle R; Leeuw, Maureen; Atiqi, Sadaf; van Vollenhoven, Ronald F; Wijbrandts, Carla A; Gerritsen, Martijn; Krieckaert, C; Dijkshoorn, Bas; Bakhlakh, Siham; et al.
Abstract : Background: Research on the disease severity of COVID-19 in patients with rheumatic immune-mediated inflammatory diseases (IMIDs) has been inconclusive, and long-term prospective data on the development of SARS-CoV-2 antibodies in these patients are lacking. Methods: Adult patients with rheumatic IMIDs from the Amsterdam Rheumatology and Immunology Center, Amsterdam were invited to participate. All patients were asked to recruit their own sex-matched and age-matched control subject. Clinical data were collected via online questionnaires (at baseline, and after 1–4 and 5–9 months of follow-up). Serum samples were collected twice and analysed for the presence of SARS-CoV-2-specific antibodies. Subsequently, IgG titres were quantified in samples with a positive test result. Findings: In total, 3080 consecutive patients and 1102 controls with comparable age and sex distribution were included for analyses. Patients were more frequently hospitalised compared with controls when infected with SARS-CoV-2; 7% vs 0.7% (adjusted OR: 7.33, 95% CI: 0.96 to 55.77). Only treatment with B-cell targeting therapy was independently associated with an increased risk of COVID-19-related hospitalisation (adjusted OR: 14.62, 95% CI: 2.31 to 92.39). IgG antibody titres were higher in hospitalised compared with non-hospitalised patients, and slowly declined with time in similar patterns for patients in all treatment subgroups and controls. Interpretation: We observed that patients with rheumatic IMIDs, especially those treated with B-cell targeting therapy, were more likely to be hospitalised when infected with SARS-CoV-2. Treatment with conventional synthetic disease-modifying antirheumatic drugs (DMARDs) and biological DMARDs other than B-cell targeting agents is unlikely to have negative effects on the development of long-lasting humoral immunity against SARS-CoV-2.